Native structure and arrangement of inositol-1,4,5-trisphosphate receptor molecules in bovine cerebellar Purkinje cells as studied by quick-freeze deep-etch electron microscopy. - Katayama, E (1996)
We used quick-freeze deep-etch replica electron microscopy to visualize the native structure of inositol-1,4,5-trisphosphate receptor (IP3R) in the cell. In the dendrites of Purkinje neurons of bovine cerebellum there were many vesicular organelles whose surfaces were covered with a two-dimensional crystalline array of molecules. Detailed examination of the cytoplasmic true surface of such vesicles in replica revealed that the structural unit, identified as IP3R by immunocytochemistry and subsequent Fourier analysis, is a square-shaped assembly and is aligned so that the side of the square is inclined by approximately 20 degrees from the row-line of the lattice. Comparison with the ryanodine receptor (RyaR), another intracellular Ca2+ channel on the endoplasmic reticulum, suggested that IP3R, unlike RyaR, has a very compact structure, potentially reflecting the crucial difference in the function of the cytoplasmic portion of the molecule.